Consumer Protection in Fintech Lending: (Study of Decision Number 438/ Pid.Sus /2020/PN Jkt.Utr in the Perspective of POJK 18/2023 and the PDP Law) - Azzahra, Khalita Putri; Satino, Satino (Journal of Law, Politic and Humanities, 2025)
The rapid growth of financial technology (fintech) in Indonesia has created new legal challenges, particularly regar ding consumer protection and personal data misuse. This study examines the implementation of consumer protection in fintech lending through District Court Decision No. 438/Pid.Sus/2020/PN Jkt.Utr and evaluates the effectiveness and fairness of the legal framework under POJK No. 77/POJK.01/2016, POJK No. 18/POJK.07/2023, and the Personal Data Protection Law (Law No. 27 of 2022). Using a normative juridical method with statutory, conceptual, comparative, and case approaches, the research analyzes how these regulations ensure legal certainty and justice for consumers. The results show that although the new regulations strengthen legal protection and ethical obligations, their effectiveness still depends on law enforcement, inter-agency coordination, and public legal awareness.